Quaternary environmental changes verified by means of alluvial fan deposits at Palmas Plateau in Paraná and Água Doce in Santa Catarina in the South of Brazil - Oliveira, Leandro (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2019)
Gravity processes such as fluxes may have a high-water content that conditions them to the rheological behavior closest to liquid (Newtonian), although they are not Newtonian; while the other mass movements may exhibit plastic rheological behavior. These differences can be expressed in alluvial fan deposits. Thus, the relative concentration of water seems to be the key to the interpretation of the resulting deposit type, as well as to suggest inferences about the level of rainfall and to make paleoenvironmental considerations. In general, the evolutionary picture of the alluvial fan suggests that the Campo de Palmas began to emerge from 24,000 years AP, due to climatic changes from the Last Glacial Maximum to the middle Holocene, representing a drier climate than the present, with torrential rainfall events. These torrential rainfalls changed the water-sediment ratio, causing alluvial fan deposits in the first-order channel at the Chopim River basin during the Holocene.